PENELITIAN KUALITATIF UNTUK MENGIDENTIFIKASI KEBIASAAN MAKAN MASYARAKAT YANG BERKAITAN DENGAN HIPERTENSI ESENSIAL DI DESA TUALANG LAMA KECAMATAN DELENG POKHKISEN KABUPATEN ACEH TENGGARA TAHUN 2018 - Lia Rosa Veronica Sinaga; Seri Asnawati Munthe; Henny Arwina Bangun; Mustika Purnama Utami (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Hypertension is closely related to human life pattern. Food is the main intake for health, but every person has different perception on what they eat. Difference in perception is highly influenced by cultural values and norms in a certain community. The objective of the research was to identify people’s eatingbehavior related to essential hypertension at Talang Lama Village, Deleng Pokhkisen Sub-district, Aceh Tenggara Regency. Bad eating behavior can cause hypertension. The reasons of informants for enjoying eating delicious food are as follows: it has good taste, it can arouse their appetite and satisfaction, the perception of consuming fatty food made of coconut milk will make the body oily, healthy, and fat, and it is an honor to serve guests with fatty food with beef. People’s eating behavior usually comes from parents. Hypertension patients can change their eating behavior to make them healthier, but some of them cannot change it and get relapse, and some of them say that they do not want to change it since they have already had hypertension. It is recommended that the health care providers prevent hypertension so that they do not have relapse and complication.